ANALISA PEMBANGUNAN MANUSIA DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT DI PROVINSI PAPUA - Charley M. Bisai; Maria Kbarek; Achmad Riyadi Pajeru (Universitas Cenderawasih, 2019)
Human development in Papua is still a central issue and is a concern of the government at the national and regional levels. If human development is in its actual position, it will have an impact on the welfare of its people. Human development uses the HDI indicator (Human Development Index) while the welfare of the community uses indicators of income per capita and poverty. Some of the objectives to be achieved from this study include to analyze: (1.) the correlation of the forming components with HDI; (2.) what components form the largest HDI; and (3.) the effect of HDI on income per capita, and poverty. This study uses secondary data with the analysis period 2010 - 2018. Data analysis was performed using correlation and regression analysis techniques. The analysis shows that: (1) All components of HDI are positively and significantly related to HDI. The AHH component has a strong relationship, while the other components are very strong. The HLS and RLS components (education index) have the greatest magnitude of the correlation coefficient so they form the dominant HDI compared to AHH and Per capita Expenditures. (2) HDI has a positive and significant effect on per capita income in Papua Province. (3). HDI has a negative and significant effect on poverty levels in Papua Province.